Mitochondrial function and dysfunction - Schapira, Anthony H. V. (Anthony Henry Vernon) (International review of neurobiology, 2002)
Mitochondria are critical to the survival of cells, therefore, it is not surprising that abnormalities in mitochondrial function may lead to human disease. This book concentrates on the biology and pathology of mitochondria, covering some ot the important basic science features of the biology of mitochondria. It then moves on to discuss the breadth of human diseases related to mitochondrial dysfunction, including Parkinson's disease, Amyotrophic Lateral Sclerosis (ALS), and Alzheimer's disease. * Provides comprehensive coverage of basic science and clinical features of mitochondrial dysfunction * Presents detailed analysis of "hot" topics in mitochondrial function and neurodegenerative diseases * Includes outstanding list of contributing authors.